Individual risk factors associated with SARS-CoV-2 infection during Alpha variant in high-income countries: a systematic review and meta-analysis - Moniz, Marta; Pereira, Sofia; Soares, Patricia; Aguiar, Pedro; Donato, Helena; Leite, Andreia (Frontiers in Public Health, 2024)
Objectives This study aimed to systematically appraise risk factors associated with SARS-CoV-2 infection in high-income countries during the period of predominance of the Alpha variant (January 2020 to April 2021). Methods Four electronic databases were used to search observational studies. Literature search, study screening, data extraction and quality assessment were conducted by two authors independently. Meta-analyses were conducted for each risk factor, when appropriate. Results From 12,094 studies, 27 were included. The larger sample size was 17,288,532 participants, more women were included, and the age range was 18–117 years old. Meta-analyses identified men [Odds Ratio (OR): 1.23, 95% Confidence Interval (CI): 1.97–1.42], non-white ethnicity (OR: 1.63, 95% CI: 1.39–1.91), household number (OR: 1.08, 95% CI: 1.06–1.10), diabetes (OR: 1.22, 95% CI: 1.08–1.37), cancer (OR: 0.82, 95% CI: 0.68–0.98), cardiovascular diseases (OR: 0.92, 95% CI: 0.84–1.00), asthma (OR: 0.83, 95% CI: 0.75–0.92) and ischemic heart disease (OR: 0.82, 95% CI: 0.74–0.91) as associated with SARS-CoV-2 infection. Conclusion This study indicated several risk factors for SARS-CoV-2 infection. Due to the heterogeneity of the studies included, more studies are needed to understand the factors that increase the risk for SARS-CoV-2 infection. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021244148, PROSPERO registration number, CRD42021244148.